The Effect of Course Schedule Density and Assignment Frequency on Burnout Syndrome in Students of The Faculty of Medicine YARSI University in 2019 And 2020 and Their Review According to Islam - Rostiana, Ajeng Nita; Rahmah, Nunung Ainur; Royhan, Aan; Arifandi, Firman (Junior Medical Journal, 2023)
Background: Burnout syndrome is a measure of physical exhaustion and mental stress that is driven primarily by pressure and job requirements. The academic demands experienced by medical students, such as busy class schedules, practicum materials, group discussions, clinical skills, final exams, to organizational activities are some of the factors that make the duties and obligations as students pile up, triggering to the Burnout syndrome. According to the Islamic view, patience and trustworthiness are a way to deal with fatigue in studying. Method: This type of research is quantitative which is done in an analytical observational manner with a cross sectional design. Questionnaires were distributed via Google form to YARSI University Medical Faculty students in 2019 and 2020. The sample in this study was 224 respondents. The statistical test uses the Chi-Square test. Results: In the study it was found that there were 125 (55%) students who had moderate burnout syndrome. Based on the results of statistical tests, there is no effect between schedule density and the frequency of assignments on burnout syndrome. Conclusion: There is no effect of the density of schedules and the frequency of assignments on burnout syndrome